Path-based modelling of business processes. (8th February 2021) - Nüßer, Wilhelm
Modelling business processes as stochastic processes has a long tradition. Most models focus on the dynamics of the complete state of the process. In this article we propose a new approach which concentrates on the stochastic paths of measurable quantities like key performance indicators. Using this concept a strong analogy to current results in statistical physics is exposed which leads to a general expression for the entropy of a business process as well as results quantifying the performance loss in processes due to fluctuations. Finally, path probabilities and averages of key performance indicators of a process are given in terms of business constraints expressed as variational principles.